2017
DOI: 10.3389/fpsyg.2017.00671
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Paths from Styles of Anger Experience and Expression to Obsessive–Compulsive Symptoms: The Moderating Roles of Family Cohesion and Adaptability

Abstract: Previous research has shown strong connections of anger experience and expression with obsessive–compulsive (OC) symptoms. Additionally, studies have demonstrated links between family environment variables and obsessive–compulsive disorder (OCD). Our study aims to integrate the perspectives from these two literatures by exploring the moderating roles of family cohesion and family adaptability in the relationship between anger proneness and suppression and OCD symptoms. A total of 2008 college students were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The reported reliability and validity of the Chinese version were good, with Cronbach's α above 0.7 and concurrent validity above 0.80 (Liu et al, 2017). The Cronbach's α in this sample was 0.95.…”
Section: The Family Adaptability and Cohesion Evaluation Scales II mentioning
confidence: 60%
See 2 more Smart Citations
“…The reported reliability and validity of the Chinese version were good, with Cronbach's α above 0.7 and concurrent validity above 0.80 (Liu et al, 2017). The Cronbach's α in this sample was 0.95.…”
Section: The Family Adaptability and Cohesion Evaluation Scales II mentioning
confidence: 60%
“…The total score ranged from 42–162 points, with higher scores indicating better family functioning. The reported reliability and validity of the Chinese version were good, with Cronbach's α above 0.7 and concurrent validity above 0.80 (Liu et al, ). The Cronbach's α in this sample was 0.95.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese version of the Family Adaptability and Cohesion Evaluation Scales II (FACES II) was used to measure family functioning [ 25 ]. The scale contained 30 items in two dimensions: adaptability and cohesion.…”
Section: Methodsmentioning
confidence: 99%
“…Research showed that a more cohesive family could help male college students alleviated the relationship between irritability and obsessive-compulsive disorder (OCD). In contrast, for female college students, family cohesion (flexible family coping strategies and communication atmosphere) could help them alleviate the relationship between suppressed anger and OCD symptoms [12]. In addition, high-level family cohesion may promote subjective well-being through high-level self-concept clarity and hope [13].…”
Section: Introductionmentioning
confidence: 99%